Gender and the Rule of Law in Transitional Societies - Hamilton, Michael (2009)
This article examines a unique relationship—specifically, the connection between the rule of law, as it is imported and experienced in post-conflict/post-repression societies, and gender. We assert that some of the most gendered and problematic dimensions of rule of law discourse and practice can arise with intensity in post-conflict or post-repressive societies. In particular, we explore a fundamental contradiction. Transitional societies bring powerful and transformative moments to global attention